2002
DOI: 10.2320/matertrans.43.2437
|View full text |Cite
|
Sign up to set email alerts
|

Superplasticity and Cavitation of Recycled AZ31 Magnesium Alloy Fabricated by Solid Recycling Process

Abstract: Superplastic behavior and cavitation have been investigated for the solid recycled AZ31 magnesium alloy made of machined chips. The elongation to failure of the solid recycled specimen was lower than that for the extruded specimen from a virgin block (virgin extruded specimen) at elevated temperature, although the strain rate sensitivity for the solid recycled specimen was the same as that for the virgin extruded specimen. The volume fraction of cavities and the total number of cavities for the solid recycled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…It was shown in the previous work 9) on the solid state recycling of a magnesium alloy that contamination of oxide particles in the solid recycled specimen promotes cavity nucleation, resulting in low elongation of the solid recycled specimen. The inhomogeneous distribution of the oxide particles shown in Fig.…”
Section: à1=2mentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown in the previous work 9) on the solid state recycling of a magnesium alloy that contamination of oxide particles in the solid recycled specimen promotes cavity nucleation, resulting in low elongation of the solid recycled specimen. The inhomogeneous distribution of the oxide particles shown in Fig.…”
Section: à1=2mentioning
confidence: 99%
“…12,13) It should be noted that remelting is not needed for the solid state recycling. In the previous works, [7][8][9] the solid recycled magnesium alloy showed high strength due to microstructural control by the plastic deformation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a solid-state recycling has been proposed as a new method for magnesium alloy scraps, [7][8][9][10][11][12][13][14][15] where magnesium scraps such as machined chips are directly recycled by hot extrusion without remelting. Because microstructural control such as grain refinement and dispersion of contaminants can be achieved due to severe deformation during recycling, the recycled materials show excellent mechanical properties of high strength, 14) ductility, 11) and superplasticity.…”
Section: Introductionmentioning
confidence: 99%
“…It is also employed as an efficient recycling process. [5][6][7] The wastes, such as machined magnesium chips or crushed in-house magnesium scraps, can be used as input raw materials by the direct hot extruding process. It is reported that solid recycled AZ31 magnesium alloy shows UTS of 268 MPa and 14% elongation, which are the same as those of the virgin extruded alloy.…”
Section: Introductionmentioning
confidence: 99%